The EFFECT OF EFFECTIVE SUPERVISION ON IMPROVING THE QUALITY OF EDUCATION IN THE ERA OF DISRUPTION - Walid, Ahmad; Sutiah, Sutiah; Shodiq , Ja’far (Antis-Publisher, 2024)
This study aims to explore the role of supervision in improving the quality of education in the era of technological disruption. A mixed approach is used by combining qualitative and quantitative elements to gain a comprehensive understanding. Data was collected through in-depth interviews with supervisors, principals, and teachers, as well as surveys of teachers in several educational institutions. Qualitative data analysis was carried out using a thematic approach, while quantitative data was analyzed using statistical techniques such as t-test and ANOVA. The results of the study show that effective educational supervision contributes significantly to improving teacher competence, integrating technology in learning, and improving student learning outcomes. Good interaction between supervisors, teachers, and school management is key to creating a conducive and innovative learning environment. The implication of this research is the importance of developing adaptive and innovative supervision strategies to support educational institutions in facing technological changes and improving the quality of education in a sustainable manner. Keywords : Educational Supervision, Education Quality, Technological Disruption